Drivers of Industry Convergence: The Case of Functional Food Industry in Indonesia - Karlina Sari; Dian Prihadyanti; Dudi Hidayat (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2019)
Food industry has been considered as industry with low-intensity research and low R&D-to-sale ratio. However, changes in the environments of food industry; changes in society’s lifestyles; the rise of world’s food consumption; a shrinking food production base; and changing perspective of society toward the consequences of the food system’s sustainability have forced food industry to innovate. Functional food is the form of innovation in food industry, where the food processing involves new scientific and technical approach. As the 4th highest-population country with rising level of life expectancy and increasing number of high-middle-income people, there is a question whether Indonesia can be a big market and player in functional food industry. This paper first presents the overview of functional food industry in Indonesia. It analyzes the prospect of Indonesian functional food industry from demand, supply, and regulation perspective. The result of this study is Indonesia should have a good prospect as both the market and the player in functional food industry. Currently, baby and toddler are Indonesia’s biggest market of functional food for baby formula milk and baby food. Another functional food market segment prospective to be penetrated is elderly who have bigger risk of disease, such as hypertension and arthritis. Player who enter this industry must have strong financial and research capacities. Research about functional compounds in local Indonesian food conducted in preliminary stage and they need to be proven on animal and human studies. Regulation about labelling and advertisement of processed food with special claim and processed food for special nutrition needs is already sufficient to ensure food safety. However, law enforcement is still weak.Keywords: functional food, healthy food, research capacity, labelling, food safety.